1964
DOI: 10.1126/science.146.3649.1316
|View full text |Cite
|
Sign up to set email alerts
|

Uricase: Localization in Hepatic Microbodies

Abstract: Microbodies of rat hepatic cells and hepatomas contain a crystalloid with the same structural characteristics as crystals of purified uricase, when viewed by electron microscopy. We conclude that crystalline uricase is located within hepatic microbodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(71 citation statements)
references
References 7 publications
6
65
0
Order By: Relevance
“…These two enzymes have been found in microbodies isolated from many kinds of cells and are considered by de Duve to be distinctive enzymes of the class of microbodies named peroxisomes (11). Uricase is another enzyme which has been found in most of the peroxisome preparations so far described (4,22,(30)(31)(32)41). It is therefore of interest that, as shown in these investigations, uricase is also present in glyoxysomes.…”
Section: Methodsmentioning
confidence: 91%
“…These two enzymes have been found in microbodies isolated from many kinds of cells and are considered by de Duve to be distinctive enzymes of the class of microbodies named peroxisomes (11). Uricase is another enzyme which has been found in most of the peroxisome preparations so far described (4,22,(30)(31)(32)41). It is therefore of interest that, as shown in these investigations, uricase is also present in glyoxysomes.…”
Section: Methodsmentioning
confidence: 91%
“…These criteria conform to published morphologic data for the identification of microbodies in rat liver (2)(3)(4)(5)(6)(7)(8)(9)15) . Furthermore, in all reacted material not a single normal-appearing, unstained microbody was observed, thus indirectly implying that the stained organelles must be the microbodies.…”
Section: Identification Of Microbodiesmentioning
confidence: 99%
“…The fine structure and enzyme content of the nucleoids of rat hepatic microbodies have been studied extensively (5,60,61) . Morphologically the nucleoids consist of parallel bundles of hollow tubules, which in cross-section have a honeycomb appearance and in longitudinal plane show a parallel packed, tubular structure (61) .…”
Section: The Relation Of the Reaction Product To The Nucleoids Of Micmentioning
confidence: 99%
See 1 more Smart Citation
“…The most conspicuous structural component of the peroxisome is a dense core, which has been described as crystalline, semicrystalline, crystalloid, or maltilamellated, mostly on the basis of electron microscopic images and is made up of regular striation with a honeycomb appearance (2). Biochemical analyses showed that the structure was made of urate oxidase (4,5). Peroxisome deficiencies participate in a variety of pathologies, including Zellweger syndrome.…”
mentioning
confidence: 99%